1997
DOI: 10.1093/clind/24.4.643
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Therapy for Diabetic Foot Infections: Comparison of Two Parenteral-to-Oral Regimens

Abstract: This prospective, randomized, multicenter trial compared the efficacy of two antibiotic regimens for treatment of foot infections in diabetic adults. Patients with infections requiring hospitalization were randomized to receive either intravenous ofloxacin followed by oral ofloxacin or intravenous ampicillin/sulbactam followed by oral amoxicillin/clavulanate (the aminopenicillin regimen) for 14-28 days. Patients with osteomyelitis were eligible for the study if the infected bone was to be removed. Of 108 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
76
1
4

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(88 citation statements)
references
References 10 publications
7
76
1
4
Order By: Relevance
“…ampicillin-sulbactam (1 to 2 g and 0.5 to 1 g) followed by p.o. amoxicillin-clavulanate (500 and 125 mg) in the treatment of diabetic patients hospitalized with foot infections; clinical success rates (cure and improvement) were 85% in the ofloxacin group and 83% in the aminopenicillin group, and microbiological eradication rates were 78 and 88%, respectively (26).…”
Section: Discussionmentioning
confidence: 99%
“…ampicillin-sulbactam (1 to 2 g and 0.5 to 1 g) followed by p.o. amoxicillin-clavulanate (500 and 125 mg) in the treatment of diabetic patients hospitalized with foot infections; clinical success rates (cure and improvement) were 85% in the ofloxacin group and 83% in the aminopenicillin group, and microbiological eradication rates were 78 and 88%, respectively (26).…”
Section: Discussionmentioning
confidence: 99%
“…Published studies variously reported treatment with intravenous [4] or oral antimicrobials [48,50], or shortduration intravenous followed by oral therapy [55]. A single randomized study compared results with oral and intravenous antibiotics [52].…”
Section: Route Of Administrationmentioning
confidence: 99%
“…On the basis of available studies, for mild to moderate infections, 1 to 2 weeks is usually effective [16], while for more serious infections, 2 to 4 weeks is usually sufficient [48,49]. A longer duration may be needed for immunocompromised patients, poorly perfused, deep, large or necrotic wounds, or osteomyelitis (vide infra).…”
Section: Duration Of Therapymentioning
confidence: 99%